2009
DOI: 10.2174/1874325000903010078
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous vs Submuscular Ulnar Nerve Transposition in Moderate Cubital Tunnel Syndrome

Abstract: Background:The surgical treatment of Cubital tunnel syndrome (CubTS) is still a matter of debate. No consensus exists about the necessity of anterior transposition of the ulnar nerve after decompression. However, this technique is fairly common in clinical practice. Material and Methodology:In the present study we compared the operative technique (incision length, operative time), postoperative care (postoperative pain and complications) and the outcome between subcutaneous transposition and submuscular transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 24 publications
(24 reference statements)
3
35
0
1
Order By: Relevance
“…Our study findings are in line with the published literature [2,[5][6][7][8][9][10][11]. In most of our patients with cubital tunnel syndrome, symptoms improved within the first year post-operatively, and returning to full activity was fast and was in about 12 days, which could be due to early initiation of ROM after operation with this surgical techniques; these results are also in consistent with previous studies [6].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study findings are in line with the published literature [2,[5][6][7][8][9][10][11]. In most of our patients with cubital tunnel syndrome, symptoms improved within the first year post-operatively, and returning to full activity was fast and was in about 12 days, which could be due to early initiation of ROM after operation with this surgical techniques; these results are also in consistent with previous studies [6].…”
Section: Discussionsupporting
confidence: 93%
“…Earlier reports have demonstrated that anterior subcutaneous transposition of ulnar nerve had good and excellent results ranging from 65% to 90% [2,[5][6][7][8][9][10][11]. Although results of this procedure has been published, but results are variable between articles [2,[5][6][7][8][9][10][11], additional studies that use reproducible preoperative and postoperative objective measures have been reported to be necessary to make a reliable decision on different surgical techniques [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these techniques place the nerve in a protected position, the necessity of long term immobilization and the potential complications such as excessive scarring especially in intramuscular transpositions and flexion contractures in submuscular anterior transpositions are disadvantages of these procedures (2,12,13). Subcutaneous transposition is an easier surgical technique with less operative time and postoperative pain, earlier postoperative mobilization and better postoperative outcome as compared to the submuscular approach (11). Local tenderness especially in thin patients with deficient subcutaneous tissue and falling of the nerve backward are the undesired outcomes of this technique (2).…”
Section: A B C D E F Uscetin I Et Al: Ulnar Nerve Compression At Thementioning
confidence: 99%
“…10 The ulnar nerve was then transposed underneath the pronator teres muscle. After that, the muscle was lengthened and sutured.…”
Section: Surgical Techniquesmentioning
confidence: 99%